Inhibitive Properties of Leaf Sheath Extract of Cocos Nucifera as Green Inhibitor for Mild Steel in HCl Medium - Rajalakshmi, R.; Safina, A.S. (Asian Journal of Chemistry, 2012)
Inhibitive properties of leaf sheath extract of cocos nucifera for the corrosion of mild steel were studied using conventional weight loss and electrochemical measurements of monitoring corrosion. The results revealed that leaf sheath extract of cocos nucifera inhibited the corrosion of mild steel. The inhibitor was found to function by being adsorbed on the surface of mild steel. The adsorption of the inhibitor followed the Langmuir and Temkin type adsorption isotherm. Optical images of the corrosion product (without inhibitor) and the corrosion product (with the inhibitor) confirmed that the inhibitor is an adsorption inhibitor. Physical adsorption mechanism at low temperature and chemical adsorption mechanism at high temperature had been proposed from the values of thermodynamic parameters obtained. Electrochemical studies reveal that the plant extracts act as mixed type inhibitors. Optical electron microscope and FTIR were carried out to confirm the investigated inhibitor was adsorbed on mild steel surface. The leaf sheath extract of cocos nucifera in HCl medium proved to be zero cost inhibitor, eco-friendly, non-toxic and highly economical.